Raman spectroscopy and density functional theory study of energetically closely separated C2′‐endo and C3′‐endo pentose forms in purine nucleoside analogue drug‐gold conjugates. (18th January 2018) - Ganbold, Erdene‐Ochir; Nguyen, Thanh Danh; Ly, Nguyen Hoang; Joo, Sang‐Woo; Li, Linzi; Kim, B. Moon
Abstract: We performed a vibrational analysis of a cyclin‐dependent kinase inhibitor as an anticancer drug using Raman spectroscopy and quantum mechanical calculations. BMK‐Y101, a purine nucleoside analogue cyclin‐dependent kinase inhibitor, was found to adsorb on gold nanoparticles as evidenced by ultraviolet–visible absorption spectroscopy. Density functional theory (DFT) calculations were introduced to examine the energetic stabilities of the tautomeric amino and imino purine rings as well as C3 ′‐endo and C2 ′‐endo pentose forms for the possible binding geometries to 6‐atom gold clusters. DFT calculations predicted that the N9 binding mode of the C2 ′‐endo amino purine conformer would be the most stable in coordination with the gold atoms, despite very small energy differences of 0.026 kcal/mol to the second stable conformer of the N1 coordinated state. Surface‐enhanced Raman scattering (SERS) spectra were analyzed with appropriate vibrational assignments according to the DFT calculations and potential energy distribution analysis. The vibrational band at ~1, 460 cm −1, which can be ascribed to the ν(N9 –C4 )(20%) + ν(N3 –C4 )(13%) + ν(C10 –C7 )(12%) + ν(C7 –C8 )(12%) + ν(N3 –C2 )(11%) mode for the N9 ‐coordination on Au6, appeared to be the most prominent in the SERS spectra, as predicted from the DFT calculations. BMK‐Y101 appeared to be detached from gold nanoparticles efficiently not in cell culture media but in hepatocarcinoma cells. Our findings indicate that quantum mechanical DFT calculations can be successfully implemented to interpret the SERS spectral features of the nucleoside drug on Au surfaces. Abstract : Density functional theory calculations can be successfully implemented to interpret the surface‐enhanced Raman scattering spectral features of the nucleoside drug of energetically closely separated C2 ′‐endo and C3 ′‐endo pentose form on Au.